PENGARUH”DOW JONES ISLAMIC MARKET INDEKS (DJIM),”DOW JONES ISLAMIC MARKET INDEKS(DJIM) CHINA,”DAN INDEKS HARGA SAHAM GABUNGAN (IHSG)“TERHADAP JAKARTA ISLAMIC INDEKS (JII) PRIODE 2014-2018 - Agus Salihin (UIN Mataram, 2019)
The purpose of this study was to determine the effect”of the Dow Jones Islamic Market Index (DJIM)” the Dow Jones Islamic Market Index (DJIM) of China, and the Composite Stock Price Index (CSPI) of”the Jakarta Islamic Index (JII) for the 2014-2018 period.”This type of research uses quantitative”descriptive. The data used are secondary data with monthly data period of 1 June 2014-31 December 2018. The”data analysis technique is”using multiple linear”regression. The results of the study”can show that partially the Dow Jones Islamic Market Index (DJIM) and the Composite Stock Price Index (CSPI) have a positive effect on the Jakarta Islamic Index (JII) for the 2014-2018 period. While the Dow Jones Islamic Market Index (DJIM) of China did not have a positive effect on the Jakarta Islamic Index (JII) for the 2014-2018 period. Simultaneously the Dow Jones Islamic Market Index (DJIM),”China Dow Jones Islamic Market Index (DJIM), and the Composite Stock Price Index”(CSPI) significantly influence the”Jakarta Islamic index (JII) for the 2014-2018 period.”From the results of the analysis of the coefficient of determination (Adjusted R Square) the Dow Jones Islamic Market Index (DJIM) variable, the”Dow Jones Islamic Market Index (DJIM), and the Composite Stock Price Index (CSPI) can affect the Jakarta Islamic Index for the 2014-2018 period by 80.7% . while the remaining 19.3% is influenced by other variables.